Mild encephalopathy with reversible extensive white matter lesions in a child with acute adenoviral infection and a literature review - Akın, Mustafa Emre; Çıtak-Kurt, Ayşegül Neşe; Bayhan, Gülsüm İclal; Ezgü, Zeynep Dinçer; Bulut, Sevtap Şimşek (The Turkish Journal of Pediatrics, 2021)
Background. Mild encephalopathy with a reversible splenial lesion (MERS) is a known clinical-radiological description. However, MERS with extensive lesions (MERS type-2) is rarely associated with adenovirus. There are only three published cases of MERS type-2 associated with adenovirus infection. Case. We present a 10-year-old previously healthy girl who presented with speech difficulty and mild encephalopathy after three days of prodromal illness. The magnetic resonance imaging (MRI) revealed bilateral diffusion restriction in the parietal white matter, splenium and genu of the corpus callosum without mass effect and slight thickening at the splenium of corpus callosum with no contrast enhancement. With empirical and support treatment, her neurological examination was completely normal by the 18th hour. The nasopharyngeal respiratory adenoviral PCR resulted positive. She was discharged with total clinical and radiological resolution on the 10th day of admission. The case was diagnosed with MERS type-2 which is rarely associated with adenoviral infection. Conclusion. This report is the first case of adenovirus related MERS type-2 in a Turkish child. Pediatricians, child neurologists, child infection specialists and radiologists should recognize this condition to ensure appropriate diagnosis.
Keywords: adenovirus; child; corpus callosum; encephalopathy